2015
DOI: 10.1099/jmm.0.023036-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial antimicrobial metal ion resistance

Abstract: Metals such as mercury, arsenic, copper and silver have been used in various forms as antimicrobials for thousands of years with until recently, little understanding of their mode of action. The discovery of antibiotics and new organic antimicrobial compounds during the twentieth century saw a general decline in the clinical use of antimicrobial metal compounds, with the exception of the rediscovery of the use of silver for burns treatments and niche uses for other metal compounds. Antibiotics and new antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
230
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 329 publications
(252 citation statements)
references
References 243 publications
(204 reference statements)
6
230
0
16
Order By: Relevance
“…E. coli express genes encoding ZntA for Zn 2+ efflux, CopA for Cu + efflux, and the CusCBA complex for periplasmic Cu + efflux, but virulent strains have additional copper resistance systems Senftenberg, or Tennessee isolates (Qin et al 2014). This genetic cluster is comprised of two previously reported metal ion resistance determinants, neither of which was realized until recently to be part of a single contiguous gene cluster (Crossman et al 2010;Hobman and Crossman 2015). One, the pco determinant was first isolated from plasmid pRJ1004 from an Australian pig E. coli isolate (Brown et al 1995) and confers copper resistance.…”
Section: Introductionmentioning
confidence: 99%
“…E. coli express genes encoding ZntA for Zn 2+ efflux, CopA for Cu + efflux, and the CusCBA complex for periplasmic Cu + efflux, but virulent strains have additional copper resistance systems Senftenberg, or Tennessee isolates (Qin et al 2014). This genetic cluster is comprised of two previously reported metal ion resistance determinants, neither of which was realized until recently to be part of a single contiguous gene cluster (Crossman et al 2010;Hobman and Crossman 2015). One, the pco determinant was first isolated from plasmid pRJ1004 from an Australian pig E. coli isolate (Brown et al 1995) and confers copper resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Many others are required for cellular function, such as Zn and Cu, but can be toxic in excess. Cells have thus developed many ways to regulate intracellular metal concentrations (1)(2)(3)(4)(5)(6)(7)(8)(9). Metal-responsive transcriptional regulation is one of them, where metalloregulators respond to intracellular metal ions and regulate transcription of metal efflux, uptake, or other metal homeostasis genes (4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Several studies have shown that bacteria of the genus Pseudomonas are highly resistant to the different forms of Hg (Hobman and Crossman, 2015;Ndu et al, 2016) and have been reported in great abundance in waste high in Hg concentrations.…”
Section: Identification Of the Microorganismsmentioning
confidence: 99%
“…Although Hg is toxic to both eukaryotic and prokaryotic cells, some microorganisms have developed resistance mechanisms to the metal (Hobman and Crossman, 2015).…”
Section: Introductionmentioning
confidence: 99%